Optimizing Lunar Descent Efficiency Using Reinforcement earning: A Computational Physics Investigation of Fuel-Constrained Landing Dynamics (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Planetary landings can only be autonomous by having control systems that are able to balance accuracy and efficiency under nonlinear conditions.This research project examines the use of reinforcement learning (RL) which in this case is Proximal Policy Optimization (PPO) algorithm to simulate and optimize the dynamics of lunar descent in a one dimensional environment with Newtonian physics.The agent was trained to successfully complete soft landings at different fuel and thrust-cost settings, where a reward function punished the use of fuel and high terminal velocity.On 40 000 training episodes, the agent always shared similar stable policies that reduced fuel usage and yet reached safe touchdown speeds (less than 2 m/s-1).Quantitative analysis showed the existence of a strong negative correlation between available fuel and final velocity and unique dual-phase kinetics of fuel-use patterns were found which were similar to real-world powered-descent sequences.These findings confirm that reinforcement learning is a physically consistent, adaptive control technique to optimize descent, and has the potential to be useful in autonomous guidance systems in future trips to the moon and other planets.